2020
DOI: 10.1111/pops.12696
|View full text |Cite
|
Sign up to set email alerts
|

Antiwomen But Proquota: Disaggregating Sexism and Support for Gender Quota Policies

Abstract: Previous research on support for gender quotas focuses on attitudes toward gender equality and government intervention as explanations. We argue the role of attitudes toward women in understanding support for policies aiming to increase the presence of women in politics is ambivalent—both hostile and benevolent forms of sexism contribute in understanding support, albeit in different ways. Using original data from a survey conducted on a probability‐based sample of Australian respondents, our findings demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 59 publications
(92 reference statements)
2
12
0
1
Order By: Relevance
“…Finally, we found that benevolent sexism was related to increased support for the #MeToo Movement. Although this was not an expected finding, it squares with the protective nature of benevolent sexism and is consistent with research that has found a positive relationship between benevolent sexism and support for gender quotas and even compliance with public health measures (Chen and Farhart, 2020;Beauregard and Sheppard, 2021). This connection raises important questions for how men view this movement and the strategies that political leaders and activists should take in pushing for more progressive policies.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, we found that benevolent sexism was related to increased support for the #MeToo Movement. Although this was not an expected finding, it squares with the protective nature of benevolent sexism and is consistent with research that has found a positive relationship between benevolent sexism and support for gender quotas and even compliance with public health measures (Chen and Farhart, 2020;Beauregard and Sheppard, 2021). This connection raises important questions for how men view this movement and the strategies that political leaders and activists should take in pushing for more progressive policies.…”
Section: Discussionsupporting
confidence: 83%
“…Hideg et al (2016) find that benevolent sexism is associated with more support for employment equity policies supporting women, but this support did not extend into more stereotypically masculine workplace settings. Hostile sexists are less likely to support the adoption of gender quotas to increase women's representation in politics, whereas benevolent sexists are more likely to support these policies even though they do not support gender equality generally (Beauregard and Sheppard, 2021). Hostile sexism predicts victim-blaming attributions for the gender gap in income inequality (Connor and Fiske, 2019) as well as opposition to breastfeeding in public (Huang et al, 2020) and tolerance for sexual harassment (Russell and Trigg, 2004).…”
Section: The Impact Of Sexism On Policy Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter, by contrast, reflects paternalistic ideas about women's role in society, such as a belief in women's greater purity and their need for men's protection. Beauregard and Sheppard (2021) shows that benevolent, but not hostile, sexists are more likely to support gender quotas in order to bring 'women's perspectives' into policymaking.…”
Section: Gendered Institutions and Clash Of Valuesmentioning
confidence: 99%
“…Gothreau et al (2022:2-3) para el caso de EEUU, identificaron que el sexismo benévolo está asociado con un mayor apoyo a las políticas de equidad laboral que reivindican a las mujeres, pero donde dicho discurso no es posible que se vea extendido a entornos laborales más estereotipados con discursos sexistas hostiles. En ese mismo artículo se afirma que es menos probable que las personas con discursos sexistas hostiles apoyen la adopción de cuotas de género para aumentar la representación de las mujeres en la política, mientras que es más probable que las personas con discursos sexistas benévolos apoyen dichas políticas aunque no apoyen la igualdad de género -y el feminismo-en general (Beauregard y Sheppard 2021). Los discursos sexistas hostiles muestran mayor disposición a responsabilizar a las víctimas por la desigualdad de género (Connor y Fiske 2019) y una mayor tolerancia al acoso sexual (Russell y Trigg 2004;Gothreau et al 2022:4).…”
Section: ¿Qué Se Entiende Por Sexismo En Torno a Las Afirmaciones Pro...unclassified